Deleuze and Guattari: Geophilosophy and Historical- Geographical Narratives of the Balkans (Global Journal of Human-Social Science, 2022)
Geophilosophy is a spatial concept that will be applied as a supplement to the geographical method with the aim of better understanding the historical-geographical conditionality in the Central Balkans 1 its political-geographical evolution and the variability of regional-geographical forms 2 As a philosophical concept geophilosophy was created by Deleuze and Guattari 1995 at the end of their scientific careers From their philosophical point of view Tampio 2014 Protevi 2010 Parr 2010 and others wrote about their work This concept also has its geographical dimension and significant results have been written about it by Woodward 2017 Bonta 2010 Peet 1998 and others All these authors emphasize the importance of the book A Thousand Plateaus 2013 A form of new materialism with a politicized philosophy of differences was successfully developed and in which the meaning of geophilosophy is created through the superposition of layers of thought Although indications of geophilosophy can be recognized in Nietzsche s works and the whole concept can be interpreted as a philosophical aspect of geographical geological processes this concept has a far more complex meaning poststructuralism This paper aims to apply geophilosophy as a method in interpreting complex historical-geographical processes which in addition to their complexity and long duration can also indicate their certain regularity The theoretical basis for this approach is sought through Deleuze s and Guattari s 1995 121 view of the importance of the milieu the notion through which they show that philosophy is a certain geophilosophy just as in Braudel s view history is a certain geohistory and that to present through ancient Greece allusion to the past of philosophy modern Europe present philosophy while the process of emergence represents the future of philosophy Lundy 2011 116 interprets this so that exceptional geographical circumstances determine the nature of thought and that the nature of each milieu is as historical as it is geographical In this paper the miles of ancient Greece will be transposed to the neighboring Balkans and then explained through three processes territorialization deterritorialization and reterritorialization that will produce recognizable historical and geographical narratives
Keywords: geophilosophy; territorialization; deterritorialization; reterritorialization; milieus; balkans